Bone fracture risk in patients with rheumatoid arthritis: A meta-analysis. Issue 36 (September 2017) - Xue, A-Li; Wu, Su-Ye; Jiang, Lei; Feng, Ai-Mei; Guo, Hai-Fei; Zhao, Pu
Abstract: Background: Patients with rheumatoid arthritis (RA) are predisposed to osteoporotic fracture. The present study aims to determine the association between rheumatoid arthritis (RA) and bone fracture risk, and in relation to gender and site-specific fractures. Methods: Studies related to bone fracture in patients with RA were searched from databases including PubMed, EMBASE, and OVID from inception through April 2016. The quality of the studies was evaluated using the Newcastle-Ottawa Scale. Meta-analysis was performed with Stata13.1 software. The results were reported based on risk ratio (RR) and 95% confidence interval (95% CI) using a random effects model. Results: The meta-analysis of 13 studies showed a significant higher risk of bone fracture in patients with RA than in patients without RA (RR = 2.25, 95% CI [1.76–2.87]). Subgroup analyses showed that both female and male patients with RA had increased risk of fracture when compared with female and male patients without RA (female: RR = 1.99, 95% CI [1.58–2.50]; male: RR = 1.87, 95% CI [1.48–2.37]). Another subgroup analysis of site-specific fracture also showed that RA is positively correlated with the incidence of vertebral fracture (RR = 2.93, 95% CI [2.25–3.83]) or hip fracture (RR = 2.41, 95% CI [1.83–3.17]). Conclusion: RA is a risk factor for bone fracture in both men and women, with comparable risks of fractures at the vertebral and hip.